Study on the role of rGO in enhancing the electrochromic performance of WO3 film. (20th September 2022) - Bhattacharjee, Saheli; Sen, Sovandeb; Samanta, Soumya; Kundu, Susmita
Highlights: An improved rGO incorporated WO3 based electrochromic film was developed using a facile sol-gel dip-coating procedure. 5wt% rGO composition demonstrated the maximum electrochemical performance along with 50% transmittance modulation. ∼ 45% enhancement in the switching response time and a significant improvement in coloration efficiency were also obtained. The observed better electrochemical cyclic stability of rGO-WO3 film was analyzed using ex-situ XRD analysis. The EIS study of pristine and rGO decorated films revealed enhanced charge transfer on incorporation of rGO. Abstract: In the present work, an improved electrochromic thin film has been developed with faster color switching time on incorporation of rGO in WO3 film. Here, pristine WO3 and rGO-WO3 (rGO concentration varying from 1–7wt%) based nanocomposite electrochromic films were fabricated on ITO coated glass substrate, by utilizing a facile sol-gel dip-coating technique. Detailed structural and morphological analyses of the films were carried out using XRD, FESEM, TEM and Raman Spectroscopy. Assimilating the electrochromic properties of all the films showed that, 5wt% rGO incorporated WO3 film gave a maximized electrochemical performance with minimum degradation in optical transmittance. The film also exhibited an optical modulation of ∼ 50% and a better switching response having coloration time (tc ) ~ 5.3 s and bleaching time (tb ) ~ 6.2 s as compared to the pristine film (tc ~ 9.6 s, tb ~ 10.4 s). Incorporation of rGO also resulted in an enhancement of coloration efficiency from ∼ 81 to ∼ 386 cm 2 /C. The Electrochemical Impedance Spectroscopy (EIS) analysis of pristine and rGO loaded film clearly revealed better charge transfer on incorporation of rGO. The cyclic stability study exhibited ∼ 25% deterioration in optical transparency of the bare WO3 film which was < 10% for the rGO impregnated film. An ex-situ XRD analysis demonstrated that a crystal dislocation occurring in pristine WO3 sample was responsible for the same. Graphical abstract: Image, graphical abstract .